The analysis on functionality of composite solder oxidize copper lead frame interconnect in microelectronic packaging - Ahmad, Intan Fatihah (2022)
Recently, the attention toward CNT-composite solder (CCS) has increased remarkably due to numerous advantages. However, the electronic devices’ failure is still growing and has become an integral part of the countless product in the industrial market. These failures are mainly related to the reliability of electronic packaging. The significant reliability degradation because the solder has lifted due to the occurrence of the oxide layer on the copper lead frame’s surface. Hence, the primary purpose of this study is to analyse the performance of the CCS on the copper lead frame, especially on the oxidise copper lead frame. Nonetheless, the reflow temperature for CCS was first acquired to ensure the uncertainty on data validity could be eliminated. In this study, the commercial solder SAC 305, subjected to different weight percentages (Wt.%), was reflowed on the oxidise copper substrate to analyse the performance of CCS when encountering the oxidise copper lead frame. The CCS subjected to the different weight percentages of carbon nanotube was first characterised to investigate the effect of carbon nanotube on the CCS’s properties. Then, the copper lead frame, which undergoes a heat treatment process subjected to four different temperatures (60 ºC, 120 ºC, 180 ºC, and 240 ºC), was analysed to ensure the existence of an oxide layer on the copper lead frame’s surface. Apart from that, scrutinise the effect of the oxide layer on the copper lead frame’s properties. Afterwards, the CCS was reflowed on the oxidise copper lead frame, and the IMC’s microstructure of the CCS will be observed through TEM. The CCS is stiffened as the amount of the CNT incorporated into the commercial solder increases. The hardness of the CCS was increased from 15.75 Hv to 17.20 Hv, 17.33 Hv and 18.5 Hv as the wt. % of the CNT increased from 0.01 to 0.02, 0.03 and 0.04. However, the Young modulus for CCS with 0.01 CNT, which is 3.41x10-4 N/mm decreased to 1.5x10-4 N/mm as the 0.02 wt.% of CNT was added into the solder and increased to 2.37x10-4 N/mm and 4.06x10-4 N/mm as the 0.03, and 0.04 wt.% was added into the solder. For the oxidising copper lead frame, the native oxide layer already existed on the copper lead frame’s surface, and the thickness was 6 nm. The thickness of the oxide layer increased to 10 nm, 19 nm, 110 nm and 350 nm after the copper lead frame was exposed to the temperatures of 60 ºC, 120 ºC, 180 ºC and 240 ºC. In addition, the conductivity of the copper lead frame decreased from 58.71 %IACS to 47.2 %IACS and 44.57 %IACS when the copper lead frame was exposed to 60 ºC and 120 ºC. The conductivity value of the copper lead frame started to increase to 45.41 %IACS and 52.33 %IACS when the copper lead frame was exposed to 180 ºC and 240 ºC. The presence of the intermetallic compound (IMC) after the CCS reflowed on the oxidise copper lead frame proves that the CCS was successfully joining with the copper lead frame. The void has spotted lies at the surface of the oxidise copper lead frame and along with the IMC layer. The occupancy of voids along the IMC layer will degrade the reliability of the CCS solder. In conclusion, the commercial solder’s properties were improved when added with CNT, but the void may develop within the IMC layer when encountered with the oxidise copper lead frame. The void will reduce the life span of the joint. This study’s finding profoundly emphasises the knowledge of the CNT-composite solder and when reflowed on the oxidise substrate.